Geochemical signatures and nanomechanical properties of echinoid tests from nearshore habitats of Florida: environmental and physiological controls on echinoid biomineralization - Przemysław Gorzelak; Luis Torres Jr.; Dorota Kołbuk; Tobias B. Grun; Michał Kowalewski (PeerJ)
The mechanisms that regulate minor and trace element biomineralization in the echinoid skeleton can be primarily controlled biologically (i.e., by the organism and its vital effects) or by extrinsic environmental factors. Assessing the relative role of those controls is essential for understanding echinoid biomineralization, taphonomy, diagenesis, and their potential as geochemical archives. In this study, we (1) contrast geochemical signatures of specimens collected across multiple taxa and environmental settings to assess in situ the effects of environmental and physiological factors on skeletal biomineralogy; and (2) analyze the nanomechanical properties of the echinoid skeleton to assess potential linkages between magnesium/calcium (Mg/Ca) ratios and skeletal nanohardness. Live specimens of sand dollars and sea biscuits (Mellita tenuis, Encope spp., Leodia sexiesperforata, and Clypeaster subdepressus) were collected from three different salinity regimes: (1) a coastal region of Cedar Key influenced by freshwater input from Suwannee River, with low and fluctuating salinity; (2) St. James Bay with less fluctuating, higher salinity; and (3) Florida Keys with stable, fully marine salinity conditions. No clear relationship was found between the bulk skeletal barium/calcium (Ba/Ca), zinc/calcium (Zn/Ca), sodium/calcium (Na/Ca), cadmium/calcium (Cd/Ca), copper/calcium (Cu/Ca), phosphorous/calcium (P/Ca), lead/calcium (Pb/Ca), boron/calcium (B/Ca), manganese/calcium (Mn/Ca) ratios pooled across all taxa. In contrast, bulk Mg/Ca, strontium/calcium (Sr/Ca), sulfur/calcium (S/Ca) and lithium/calcium (Li/Ca) ratios exhibited notable differences between the three regions, indicating that distribution of these elements can be at least partly influenced by environmental factors such as salinity. However, such patterns were highly variable across taxa and regions, indicating that both environmental and physiological factors influenced geochemical signatures to varying degrees, depending on the species and environmental setting. In addition, regardless of species identity, different types of stereom within single tests were characterized by distinct skeletal Mg/Ca ratios and nanohardness. The inner galleried and coarse labyrinthic stereom typically exhibited a lower Mg/Ca ratio and nanohardness than the outer imperforate stereom layer that locally forms tubercles. Such heterogeneity in Mg distribution within single specimens cannot be ascribed solely to environmental changes, indicating that these echinoids actively regulate their intraskeletal Mg content: the higher magnesium concentration at the tubercles relative to that of the underlying stereom may be interpreted as a strategy for enhancing their mechanical strength to withstand surface friction and wear. The results suggest that the trace element composition of echinoid tests is a complex outcome of environmental and physiological factors.